Batasan Kewenangan Otoritas Jasa Keuangan terhadap Lembaga Keuangan Mikro Berbentuk Badan Hukum Koperasi - Wisuda, Selvia (University of Merdeka Malang, 2023)
The Financial Services Authority is an independent institution and free from interference from other parties which has the functions, duties and authority of regulation, supervision and protection. One of the institutions that is also supervised by the Financial Services Authority is a Cooperative which is part of a Microfinance Institution which is a legal entity. One of the objectives of the Financial Services Authority's supervision is to protect customers from various problems with financial institutions. This research is normative juridical legal research by examining and approaching various legal rules that regulate the existence of regulations regarding the authority possessed by the Financial Services Authority. By reviewing and approaching various legal rules that regulate the existence of regulations regarding the authority possessed by the Financial Services Authority. Consumer protection that can be carried out by the Financial Services Authority is through complaint, investigation, reporting and prosecution mechanisms. The principles of Microfinance Institutions include justice, togetherness, independence, convenience, openness, equity, sustainability, and effectiveness and effectiveness. The role of the Financial Services Authority in terms of customer protection is in the form of consumer complaint services which include preparing adequate equipment, creating a consumer complaint mechanism, and facilitating complaint resolution.